PROBLEMS OF TRANSLATING PERSIAN WORDS INTO THE KAZAKH LANGUAGE IN TURKIC-ISLAMIC MANUSCRIPTS - М., Өзaрслaн; З., Шaдкaм (Journal of Oriental Studies, 2019)
The first written work has appeared Karahanlı Turkish Islamic period. These works contain extensive and deep information about the history, society and state structure of the Turks, language, belief and philosophy of life. Various researches and studies about Atabet ulHaqayiq, Kutadgu Bilig, Divani L gati atT rk, Divani Hikmet that is the most important works of this period have been made and continue to be done. Many scientific studies have begun to be carried out in Kazakhstan in recent years. In fact, extensive support has been made by the Kazakhstan State under the project “Medeni Mura” in other words Cultural Heritage. However, we think that the characteristics of language and alphabet of these works, which unites the Turkish world around common beliefs and ideas, are not considered sufficiently. It is possible to say that the influence of ancient Iranian culture and belief is obviously seen in these great works based on studies of Turkish, Kazakh, Persian and Russian. The use of Persian words take attantion among these effects. We will try to evaluate in our work, the writing of the words of Pahlavi and the ancient Persian; examinations of their meanings and usage; explain that these words are used in today’s Kazakhstan with the examples and the studies on this subject in recent years in Kazakhstan. Key words: Karahanl period, TurkishIslamic works, Iranian culture, Kazakh, Persian.